Code-switching in Gol & Gincu - Mohamed Nil, Zurina; Paramasivam, Shamala (Elsevier, 2012)
There are a lot of research concerning code-switching, both in the local and international context. However, this study examines a different aspect of code-switching. It analyses the use of code-switching in the media specifically in a movie. The study aims to understand code-switching in the mediated form in a Malaysian movie; Gol & Gincu. The study examines the macro and micro functions of code-switching in this movie. It was found that some of the macro functions of code-switching included Speech Accommodation, Construction of Identity and to Exhibit Power. Within these macro functions, there were a variety of micro functions embedded within the discourse. The significance of the study is on how the macro and micro functions of code-switching in the movie Gol & Gincu may be reflective of code-switching in real life communication in Malaysian Society particularly the urban community.